Differences in The Measurement of The Right And Left Form of Blood Pressure in Hypertension Patients - Nurmoko, Anang; Fadilah, Ana; Pujiati, Eny (South East Asia Nursing Research, 2020)
Hypertension is one of the number one causes of death, globally. Hypertension is the most common cause of cardiovascular events and is a major problem in both developed and developing countries. Cardiovascular is also the number one cause of death in the world every year. Respondents in this study were patients with a diagnosis of hypertension in hospitalized patients at Mardi Rahayu Kudus Hospital, totalling 41 people. the characteristics of hypertension patient respondents seen from the age of the most patients are in the late adult age category (36-45 years), namely 31 people (75.6%), while for early adulthood (26-45 years). 35 years) as many as 10 people (24.4%). The characteristics of hypertension patient respondents seen from the sex of the most patients were male, namely 25 people (61.0%), while the female gender was 16 people (39.0%). Results The highest systolic blood pressure was 170 mmHg and the lowest was 145 mmHg. The average systolic blood pressure was 152.90 mmHg. In hypertensive patients on the left arm, the highest systolic blood pressure was 170 mmHg and the lowest was 145 mmHg. The average systolic blood pressure was 152.90 mmHg. Based on the dependent t-test, the t value is -12.491 with a p-value of 0.000. It can be seen that the p-value is 0.000 < (0.05), this indicates that there is a significant difference in the results of blood pressure measurements between the right arm and the left arm in hypertensive patients in the inpatient room of Mardi Rahayu Kudus Hospital. The difference in blood pressure variations obtained in this study is still considered normal because the difference in MAP between the right and left arms is 6.11 mmHg (normal 10-20 mmHg).